X-ray Synchrotron Polarization from Turbulent Plasmas in Supernova Remnants. Issue Volume 12:Issue S331(2017) (17th October 2017) - Baring, Matthew G.
Abstract: As supernova remnants (SNRs) age, they become efficient cosmic ray accelerators at their outer shell shocks. The current paradigm for shock acceleration theory favors turbulent field environs in the proximity of these shocks, turbulence driven by current instabilities involving energetic ions. With the imminent prospect of dedicated X-ray polarimeters becoming a reality, the possibility looms of probing turbulence on scales that couple to the super-TeV electrons that emit X-rays. This paper presents model X-ray polarization signatures from energetic electrons moving in simulated MHD turbulence of varying levels of "chaos." The emission volumes are finite slabs that represent the active regions of young SNR shells. We find that the turbulent field energy must be quite limited relative to that of the total field in order for the X-ray polarization degree to be as strong as the radio measures obtained in some remnants. Results presented are pertinent to the planned IXPE and XIPE polarimeters.